PROSEDUR PENGUJIAN SUBSTANTIF ATAS AKUN PENDAPATAN PT. A OLEH KANTOR AKUNTAN PUBLIK JEPTHA NASIB & JUNIHOL - Intan Setiawan Putri (2022)
Substantive testing of revenue accounts is a process carried out to test and detect material misstatements that can affect the correctness of income balances in the financial statements. Revenue is an account that is very susceptible to manipulation so that it can affect the financial statements of a company, especially in the income statement. Therefore, in carrying out substantive testing, it must be based on the standards that have been set in the audit program so that the audit process can be more structured. Substantive testing of revenue accounts was carried out by the Public Accounting Firm Jeptha Nasib & Junihol on PT. A is engaged in the field of Information Communication and Technology (ICT). The implementation of substantive testing on revenue accounts begins with the audit planning stage, namely assembling an audit team, preparing audit engagements, submitting requests for client data in the form of general information and company financial statements, determining materiality, and preparing audit programs. Furthermore, the field work stage is carried out, namely checking the details of income, determining samples, compiling inspection work papers, and conducting vouching. After all substantive tests have been carried out, it can be concluded that the revenue account at PT. A has been fairly stated and no material misstatement was found.